Nutrient recovery from wastewater treatment by ultrafiltration membrane for water reuse in view of a circular economy perspective - Cosenza, Alida; Gulhan, Hazal; Maida, Carmelo Massimo; Mannina, Giorgio (Elsevier BV, 2022)
The study aims to recover nitrogen from wastewater by employing ultrafiltration membrane in water reuse for agriculture purpose. To such aim, a new reclaimed water quality index (RWQI) is proposed and applied including an innovative protocol for its assessment. Specifically, the influence of filtration and backwashing times for an ultrafiltration system aimed to nutrient recovery has been analyzed. The final goal was to pin down the trade-off between operation costs and effluent quality. Results show that backwashing time play a crucial role in reducing the operation costs; indeed, low values (i.e., 0.5 min) lead to an increase in the number of required chemical cleanings and consequently operation costs (namely, up to 0.042 €/m3). The compromise among effluent quality and operation costs has been obtained for 7 min and 1 min, filtration and backwashing, respectively.
Keywords: Nitrogen; Ultrafiltration; Wastewater treatment; Wastewater; Settore MED/42 - Igiene Generale E Applicata; Waste Disposal, Fluid; Water Purification; Nutrients recovery; Waste Water; Membranes; Settore ICAR/03 - Ingegneria Sanitaria-Ambientale; Reclaimed water quality index; Waste Disposal; Membranes, Artificial; Fouling; Ultrafiltration membrane; Nutrients; Artificial; Fluid